The Effect of Family-Centered Psycho-Education on Mental Health and Quality of Life of Families of Adolescents with Bipolar Mood Disorder: A Randomized Controlled Clinical Trial - Farkhondeh Sharif; Asyeh Mahmoudi; Ali Alavi Shooshtari; Mehrdad Vossoughi (International Journal of Community Based Nursing and Midwifery, 2016)
Background: Bipolar Mood Disorder (BMD) is a type of mood disorder which is associated with various disabilities. The family members of the patients with BMD experience many difficulties and pressures during the periods of treatment, rehabilitation and recovery and their quality of life (QOL) is threatened. In the present study, we aimed to evaluate the effect of family-centered education on mental health and QOL of families with adolescents suffering from BMD. Methods: In this randomized controlled clinical trial performed on 40 families which were mostly mothers of the adolescents with BMD referred to the psychiatric clinics affiliated to Shiraz University of Medical Sciences during 2012-13.They were randomly assigned to intervention and control groups. Results: The results of single factor multivariate ANOVA/single-factor multivariate analysis of variance and Bonferroni post hoc tests showed that the interaction between the variables of group and time was significant (P<0.001). The mean of QOL and mental health scores increased in the intervention group, but it decreased in the control group at three measurement time points. Conclusion: The study findings confirmed the effectiveness of family-centered psychoeducation program on Mental Health and Quality of life of the families of adolescents with Bipolar Mood Disorder.